Impact of science on African agriculture and food security [ - Anandajayasekeram, P. (CABI, 2007)
The need for agricultural research resources in the developing world cannot be underestimated, but the availability of such resources is often poor. This book explores the importance of impact assessment studies in Africa, and assembles evidence to pave the way for investment in agricultural research all over the developing world.